2011
DOI: 10.4061/2011/254321
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Pediatric Cardiac Surgical Outcome Using Risk Stratifications at a Tertiary Care Center in Thailand

Abstract: Objectives. To determine in-hospital mortality and complications of cardiac surgery in pediatric patients and identify predictors of hospital mortality. Methods. Records of pediatric patients who had undergone cardiac surgery in 2005 were reviewed retrospectively. The risk adjustment for congenital heart surgery (RACHS-1) method, the Aristotle basic complexity score (ABC score), and the Society of Thoracic Surgeons and the European Association for Cardiothoracic Surgery Mortality score (STS-EACTS score) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In a study by Vijarnsorn et al, enrolling 230 patients, they observed a peri-operative mortality rate of 6.1%. [14] RACHS-1 and ABC score had an acceptable predictability (AUC for RACHS-1 was 0.78; AUC for ABC was 0.74). However, the sample size raises concerns in generalizing the results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study by Vijarnsorn et al, enrolling 230 patients, they observed a peri-operative mortality rate of 6.1%. [14] RACHS-1 and ABC score had an acceptable predictability (AUC for RACHS-1 was 0.78; AUC for ABC was 0.74). However, the sample size raises concerns in generalizing the results.…”
Section: Discussionmentioning
confidence: 93%
“…[23] In the present study, ACC scoring system along with ABC and RACHS-1 systems were included, and predictive abilities were assessed with NRI and IDI in addition to ROC-AUC, which are the newer metrics of assessing risk assessment models. [7] Many issues like age at operation, [14] malnutrition, repeated respiratory infections, late diagnosis and late referral for surgery, pulmonary hypertension, preoperative right ventricular dysfunction, inadequate preoperative optimization, failed percutaneous device procedures presenting as emergency surgeries and repeated congestive cardiac failure before surgery which were present in these populations, [18][19][20] are not considered in either RACHS-1 or ABC or ACC scoring models. These issues have a significant impact on the outcome as Table 1].…”
Section: Discussionmentioning
confidence: 99%
“…. These technologies also offer an easy, safe and comfortable method to monitor body temperature in pediatric patients [5]. Additionally, digital health technologies such as the iThermonitor provide a unique opportunity to caregivers to access important data (temperature readings) through the convenience of a phone or tablet computer thereby eliminating the burden of constant temperature monitoring by the caregiver.…”
Section: Caregiver Anxietymentioning
confidence: 99%
“…In both cases, fever is the first clinical sign of infection and early detection is essential to evaluate the risk for further complications and death [4,5]. Continued monitoring of body temperature may be necessary to detect any sudden changes in body temperature that may be related to a significant cause [4].…”
Section: Introductionmentioning
confidence: 99%
“…For 145 operative procedures, scores were given for potential mortality, morbidity, and technical difficulty, ranging from 0.5-5, and cumulating in a score range of 1.5-15. The score further allows grouping procedures as: level 1 (score 1.5-5.9), level 2 (score 6-7.9), level 3 (score 8-9.9), and level 4 (score [10][11][12][13][14][15]. [4][5][6] A validation study of the ABC score has been conducted from the Society of Thoracic Surgeons (STS) Congenital Heart Surgery Database and the European Association for Cardiothoracic Surgery (EACTS) Congenital Heart Surgery Database.…”
Section: Introductionmentioning
confidence: 99%